SUPPLY CHAIN VISIBILITY AND ADAPTIVE RESILIENCE FOR MSMES: CONNECTING INFORMATION QUALITY, COLLABORATIVE SENSING, AND RESOURCE RECONFIGURATION - Lili Adi Wibowo; Ricky Agusiady (Journal of Jabar Economic Society Networking Forum, 2025)
This conceptual and integrative review develops a framework for supply chain visibility and adaptive resilience in micro, small, and medium enterprises. It addresses the problem that MSMEs face disruption with thin inventories, concentrated suppliers, limited information, and little leverage, making early sensing and coordinated response strategically important. Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, and resilience, the paper explains how critical-flow mapping, information quality, collaborative sensing, contingency options, post-disruption learning can be organized as mutually reinforcing routines. The proposed pathway moves from problem diagnosis and capability mapping to bounded experimentation, evidence review, resource reconfiguration, and learning retention. No primary survey, interview, experimental, administrative, or statistical data are claimed. The framework links these mechanisms to faster response, continuity, lower dependency, recovery quality, adaptive supply networks and identifies managerial, institutional, and research implications suitable for resource-constrained enterprises.